Necessary and sufficient conditions for oscillation of first order neutral delay difference equations - Murgesan, A.; Sowmiya, P. (Global Journal of Mathematical Analysis, 2015)
In this paper, we obtained some necessary and sufficient conditions for oscillation of all the solutions of the first order neutral delay difference equation with constant coefficients of the form equation* Δ[x(n)-px(n-τ)]+qx(n-σ)=0, n≥ n_0 (*) equation*by constructing several suitable auxiliary functions. Some examples are also given to illustrate our results.